1995
DOI: 10.1016/s0741-5214(95)70242-3
|View full text |Cite
|
Sign up to set email alerts
|

Return to well-being and function after infrainguinal revascularization

Abstract: Reported health status at baseline was a predictor of improved function, mental well-being, and resolution of symptoms after infrainguinal revascularization. Expected return to "normal" may take longer than 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 19 publications
5
45
1
1
Order By: Relevance
“…In contrast, those undergoing limb salvage surgery have been reported to have reductions in physical functioning, whether or not their bypass grafts remain patent [10]. The general health status of the veterans undergoing LES in the present study was worse than that of patients undergoing infrainguinal revascularization [13].…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast, those undergoing limb salvage surgery have been reported to have reductions in physical functioning, whether or not their bypass grafts remain patent [10]. The general health status of the veterans undergoing LES in the present study was worse than that of patients undergoing infrainguinal revascularization [13].…”
Section: Discussioncontrasting
confidence: 57%
“…16 Considered together, these may suggest poorer outcome in treated patients or, even worse, may completely discourage any aggressive treatment in these patients. Previous studies from our institution have demonstrated successful limb salvage 17 and functional outcome 18 following distal arterial reconstruction in diabetic patients, with low perioperative morbidity and mortality rates. In an effort to better define the long-term outcome of these patients, we herein present our experience with a cohort of diabetic and nondiabetic patients undergoing lower extremity revascularization, with follow-up of at least 5 years.…”
mentioning
confidence: 77%
“…Some have reported significant improvements in health status 6 months after surgical revascularization. 9 Others found no difference in health status between peripheral balloon angioplasty and a medical therapy. 10 In the longest reported follow-up (mean, 9.3 years), no difference in health status existed among 77 patients who underwent peripheral balloon angioplasty.…”
Section: Editorial P 550 Clinical Perspective P 575mentioning
confidence: 99%